Whole genome sequencing to characterize monogenic and polygenic contributions in patients hospitalized with early-onset myocardial infarction - Khera, Amit V. (Circulation, 2019)
BACKGROUND: The relative prevalence and clinical importance of monogenic mutations related to familial hypercholesterolemia and of high polygenic score (cumulative impact of many common variants) pathways for early-onset myocardial infarction remain uncertain. Whole genome sequencing enables simultaneous ascertainment of both monogenic mutations and polygenic score for each individual. METHODS: We performed deep-coverage whole genome sequencing of 2,081 patients from four racial subgroups hospitalized in the U.S. with early-onset myocardial infarction (age ≤ 55 years) recruited using a 2:1 female to male enrollment design. We compared these genomes with 3,761 population-based controls. We first identified individuals with a rare, monogenic mutation related to familial hypercholesterolemia. Second, we calculated a recently developed polygenic score of 6.6 million common DNA variants to quantify the cumulative susceptibility conferred by common variants. We defined high polygenic score as the top 5% of the control distribution, as this cutoff has been previously shown to confer similar risk to familial hypercholesterolemia mutations. RESULTS: Mean age of the 2,081 patients presenting with early-onset myocardial infarction was 48 years and 66% were female. A familial hypercholesterolemia mutation was present in 36 (1.7%) of these patients and associated with a 3.8-fold (95%CI 2.1 – 6.8; p < 0.001) increased odds of myocardial infarction. 359 (17.3%) of the patients with early-onset myocardial infarction carried a high polygenic score, associated with a 3.7-fold (95%CI 3.1 – 4.6; p < 0.001) increased odds. Mean estimated untreated LDL cholesterol was 206 mg/dl in those with a familial hypercholesterolemia mutation, 132 mg/dl in those with high polygenic score, and 122 mg/dl in those in the remainder of the population. Although associated with increased risk in all racial groups, high polygenic score demonstrated the strongest association in white participants (p-heterogeneity = 0.008). CONCLUSIONS: Both familial hypercholesterolemia mutations and high polygenic score are associated with a more than three-fold increased odds of early-onset myocardial infarction. However, high polygenic score cannot be reliably identified on the basis of elevated LDL cholesterol and has a ten-fold higher prevalence among patients presenting with early-onset myocardial infarction. CLINICAL TRIAL REGISTRATION: URL: https://clinicaltrials.gov/ct2/show/NCT00597922; Unique identifier: NCT00597922